Preparation and Characterization of Lidocaine Double Layer Buccal Tablet Using Mucoadhesive Carbopol® Polymers - Sharmin, Nahid; Elias-Al-Mamun, Md; Islam, Md Saiful; Jalil, Reza-ul (Dhaka University Journal of Pharmaceutical Sciences, 2012)
The present study was intended to develop a new oral mucosal dosage form with a view of solving problems of the topical administration of Lidocaine, a local anesthetic drug, in the oral cavity. The drug was formulated as sustained release mucoadhesive bilayered tablets using mucoadhesive polymers. The first layer, consisting of a drug impermeable backing, was prepared by compression of Kollidon SR, Mg-stearate, Aerosil and talc blend in a hydrolic press at 5 ton pressure for 5 seconds. The second layer, responsible for buccal drug delivery and tablet retention on the mucosa was obtained by compression of a mixture of drug, mucoadhesive polymer and cellulose derivative for 1 min at 5 ton pressure. The tablets were evaluated in terms of swelling and water uptake and in vivo mucoadhesive performance was performed with nonmedicated tablets. In vitro drug release studies were also carried out containing fixed amount of Lidocaine (50mg), different concentrations of mucoadhesive polymer (Carbopol 934P) and hydroxypropyl methyl cellulose (HPMC). Drug release was only 30.9% in 6 hours when Carbopol 934P was used alone and at a higher concentration (240mg). Release was faster when lower concentration of polymer was used. When used in combination with HPMC, drug release was slower. In vivo mucoadhesive performance with nonmedicated tablets showed very good adherence to buccal mucosa for 6 hours and no signs of irritation was reported. Moreover, it adheres well to the gum, is not washed away by salivary fluid and is simple to apply, which indicates a better patient compliance. DOI: http://dx.doi.org/10.3329/dujps.v10i1.10012 DUJPS 2011; 10(1): 29-34